Alternative Home Financing: A Simulation Approach (Journal of Economics and Sustainability, 2022)
This paper looks at alternative financing for first-time buyers to accommodate an unprecedented occasion that may have a greater impact on homebuyers’ credibility and default risk. The existing financing under the common conventional mortgages may need to be studied to move towards Musharakah Mutanaqisah (MM) provided under Islamic financing. The simulation indicates that MM could deliver a much stable and affordable platform for buyers as the financing is on a sharing basis because the risk will be shared between the financier and the buyer. The finding also demonstrates the possibility of changing to MM as both parties could benefit even if the buyer faces total default. This simulation highlights the possibilities of alternative home financing and promoting affordable homeownership.